Social Security : The Story of British Social Progress and the Beveridge Plan - Great Britain. Inter-departmental Committee on Social Insurance and Allied Services; Davison, Ronald C. (Ronald Conway), 1884- (London : G.G. Harrap and Co., 1943)
1943 1943 1940s 3 preliminary leaves, 9-62 pages : illustrations, diagrams partly out of pride, and partly because the present remedy is to go "on the rates." Not only do many living children suffer, but, by the same token, many more are never born. In future we must solve this social problem better, if only as part of a vitally needed population policy. Cash allowances with some allowances in kind (e.g., free milk and school dinners) for children up to the school-leaving age will be a proof of our resolve to care for the nation's youth, and, if possible, restore their numbers. Such allowances cannot well be made part of our contributory social insurance system ; they must be direct State grants to the parents — to all parents irrespective of their incomes. Not that the future allowances will represent 100 per cent. of a child's maintenance! Every parent will still have to bear at least half of the full burden of maintaining his children, but in future the community will step in to share the cost. (c) Other less conspicuous gaps appear in our present social security system, but there is no space here to discuss them all. What is clear is that we can go far to abolish the remaining sub-standard living in Britain if we can effect a further moderate redistribution of income through an expanded social insurance system and children's allowances. Such poverty as still remains will be due to faults of character and non-compliance with reasonable rules. If we, as a nation, can accept this quite practicable ideal, and if our Government legislates broadly on the lines prescribed, we shall start the post-war era by setting a worthy goal for our nation and a fine example to the world. 17 15X/2/566/303